Improved exposure of curcumin-loaded nanocapsules: drug quantification in LPS-induced Drosophila melanogaster and pharmacokinetics in Wistar rats - Funghetto-Ribeiro, Ana Pozzato; Pacheco, Camila de Oliveira; Teixeira, Flávia Elizabete Guerra; Ferreira, Joane; Fernandes, Eliana; Guerra, Gustavo; Johansson Azeredo, Francine; Haas, Sandra Elisa (Frontiers in Pharmacology, 2025)
IntroductionCurcumin (CUR) has broad pharmacological potential; however, its clinical efficacy is hindered by low aqueous solubility, extensive presystemic metabolism, and poor oral bioavailability. Nanoencapsulation strategies have been proposed to overcome these limitations.MethodsWe evaluated the exposure of poly(ε-caprolactone) nanocapsules coated with polysorbate 80 containing CUR (NC-CUR) using a validated bioanalytical approach capable of quantifying CUR in whole-body homogenates of Drosophila melanogaster and in rat plasma. Healthy and LPS-challenged flies were chronically treated with CUR or NC-CUR (37 or 110 ng/mL) for 10 days through dietary exposure. Male Wistar rats received a single intravenous (2 mg/kg) or oral (6 mg/kg) dose of CUR or NC-CUR to characterize systemic pharmacokinetics.ResultsIn vitro release followed a biexponential profile, with NC-CUR showing significantly prolonged release compared to free CUR (t1/2β = 25.79 ± 0.87 h vs. 3.15 ± 1.37 h; p < 0.0001). A validated HPLC-PDA method (LLOQ = 3 ng/mL; R2 ≥ 0.997) enabled CUR quantification in whole flies and rat plasma. Chronic dietary exposure resulted in markedly higher CUR concentrations in flies treated with NC-CUR than free CUR (up to ∼200 vs. 75 ng/mL; p < 0.001), including under LPS-induced inflammatory conditions. In rats, NC-CUR increased systemic exposure following both intravenous (AUC0-∞: 1337.8 ± 385.2 vs. 100.4 ± 24.4 h⋅ng/mL; 13.3-fold, p < 0.0001) and oral administration (82.23 ± 31.68 vs. 25.55 ± 7.17 h⋅ng/mL; 3.2-fold, p < 0.01), reduced clearance (0.57 ± 0.18 vs. 7.71 ± 1.81 L/h; p < 0.0001), and accelerated absorption after oral dosing (Tmax: 0.58 ± 0.12 vs. 1.31 ± 0.28 h; p < 0.05).DiscussionNanoencapsulation significantly enhanced CUR exposure in both invertebrate and mammalian systems. This cross-species analytical strategy supports D. melanogaster as a complementary quantitative platform for early pharmacokinetic screening and reinforces NC-CUR as a promising formulation for future translational development in inflammatory conditions.